Influence of media internship on the academic performance of mass communication students of Babcock University, Ogun State, Nigeria - Sanusi, Bernice Oluwalanu (Journal of Communication and Media Research, 2018)
Internship has always been part of journalism training globally and dates back to 1906 when the University of Cincinnati in the United States first started it. Since then, no curriculum of journalism training is regarded as complete without the mandatory internship component. This study examined the influence of media attachment on the academic performance of Mass Communication students, Babcock University, Ilishan-Remo, Ogun State, Nigeria. The study adopted survey research method with questionnaire as data gathering instrument which was administered on 154 purposively selected respondents. Data obtained indicated that most of respondents were of the view that media attachment complemented classroom teaching and thus improved their academic performance. Based on this finding, the researchers concluded that media internship is fundamental to classroom learning experience of Mass Communication students. The study recommended that effective monitoring of students on media internship should be done in order to ensure that they maximize the benefits of the programme.
Keywords: Media Internship; Academic Performance; Training; Journalism